When efficiency attenuates imitation in preschool children. (24th January 2021) - Fong, Frankie T. K.; Imuta, Kana; Redshaw, Jonathan; Nielsen, Mark
Abstract : Children recognise the social value of imitation but do not opt for tools that are 'normative' if they are also dysfunctional. We investigated whether children would replicate a normative method in a tool‐learning task if it was instrumentally functional but less efficient than an alternative. Four‐ to six‐year‐old children were presented with a sticker‐retrieving task and two equally functional tool options that differed in efficiency. The inefficient tool was highlighted as the normative option. Verbal descriptors that established the normative value of the inefficient tool (e.g., 'everybody' uses this) did not motivate children to use it. The majority of children opted for instrumental efficiency over conformity.